种带储能的合力风力发电装置 (2017)
种带储能的合力风力发电装置，解决单台风车力量小，所发电力不易整合的不足，本装置采用的方案是，由组风车、传动装置和储能装置和和发电机组，组风车迎风旋转同时带动传动装置和发电机，同时向储能装置储能，当风车迎风旋转动力不足时，储能装置带动传动装置使其继续旋转或向其助力。有益效果是：组风车合力带动发电机力量大且可根据不同风场情况任意组合设置，机动灵活，风力利用率和转化效率高，能够实现风能的蓄存和释放，并转化成持续输出动能，使发电机连续运转。 A resultant-force wind power generation device with an energy storage function overcomes the shortcomings that a single windmill is small in force and the power generation force cannot be integrated easily. According to the adopted scheme, the device comprises a group of windmills, a transmission device, an energy storage device and a generator set; the group of windmills rotate windward to simultaneously drive the transmission device and the generator and store the energy in an energy storage device; when the windward rotating power of the windmills is insufficient, the energy storage device drives the transmission device to rotate continually or assists the transmission device in rotation. The resultant-force wind power generation device has the benefits that the group of windmills have a lar